Influence of retail atmospherics as nonverbal communication on purchase behaviour in the Nigerian retail environment - Kizito Ogedi Alakwe; Ngozi Okpara (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2017)
This paper focuses on unravelling the impact of atmospherics on shopper purchase behaviour in emerging markets like Nigeria and attempts to isolate the atmospheric cue that is the most significant predictor of shopper purchase decisions. The paper seeks to establish a correlation between the design, ambient and social cues in big shopping malls and buyer purchase behaviour. A quantitative and deductive approach is adopted. Data collection is through a survey, and the principal research instrument is the questionnaire. Results reveal that retail atmospherics exert some significant influence on shopper purchase behaviour. Empirical analysis indicates that retail atmospherics account for 34% of shopper purchase behaviour and that design cues are the most significant predictor of shopper purchase decision followed by ambient cues. Social cues do not exert any influence on purchase decisions. A "moderation" and "mediation" analysis revealed that though design and ambient cues influence purchase decisions independently, the interaction effect on each other is not significant. Consequently, there is a need to understand why social factors do not play a role in purchase behaviour. More importantly, there is the need to identify and understand other factors that account for the balance of 66% in shoppers' buying behaviour. Such a study might focus on factors such as pricing, sales promotion, loyalty programmes and other psycho-social factors which may work as key influencers in customers purchase decisions. For practical purposes, the focus should be on the design and ambient cues in the conceptualisation, development, and management of large retail stores.
Keywords: M30; M30; 650; retail atmospherics; ambience; shopper behaviour; shopper purchase decision; retail store environment; nonverbal communication